Integration of context awareness in Internet of Agricultural Things - Nadeem Javaid (ICT Express, 2023)
This work explores an efficient integration of IoT devices based on context awareness in the agricultural sector. A four-layered framework is proposed in which automation techniques are embedded to get real-time context aware insights from the ecosystem of IoT. The framework is evaluated using a strategic tool called threats, opportunities, weaknesses and strengths (TOWS) matrix to measure the performance of automation techniques. This analysis points out various opportunities to innovate the livelihood of agrarian society around the globe.